2022
DOI: 10.1007/s10029-022-02699-3
|View full text |Cite|
|
Sign up to set email alerts
|

Abdominal wall hernia and mental health: patients lived experiences and implications for patient care

Abstract: Background Abdominal wall hernia (AWH) affects mental health and mental health questions are frequently included within Patient-Reported Outcome Measures (PROMS) for this patient population. However, these questions have not been informed by the subjective lived experiences of mental health in AWH patients. This study is the first to qualitatively examine how AWH affects patients’ mental health. Methods Fifteen patients were interviewed from a purposive sample of AWH pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Only through using validated disease specific QoL tools, which ask questions that are important to patients, can outcomes for different treatment modalities be properly assessed. The literature review by Smith ( 2 ) identified six abdominal wall hernia specific QoL tools, each being used to assess different populations, none are universally accepted ( 1 ). The measurements covered within these abdominal wall specific QoL tools are summarised by the authors in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only through using validated disease specific QoL tools, which ask questions that are important to patients, can outcomes for different treatment modalities be properly assessed. The literature review by Smith ( 2 ) identified six abdominal wall hernia specific QoL tools, each being used to assess different populations, none are universally accepted ( 1 ). The measurements covered within these abdominal wall specific QoL tools are summarised by the authors in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Through understanding how a hernia affects the patient’s QoL, the surgeon can assess the impact that any potential surgery may have on them. Although hernia specific QoL tools exist, none are universally accepted ( 1 ), and most have been developed without patient input ( 2 ). Within hernia research, generic QoL tools are often used, however as not disease specific these may not capture key aspects important to patients with hernias ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, patients requiring AWR are often overlooked in socialist healthcare systems, given the non-life-threatening nature of their condition. Despite their relatively benign status, complex hernias carry a heavy QoL burden [5], including repercussions on mental health, disruption of daily activities of living, and recurrent bowel obstruction [6,7]. Consequently, AWR patients often display a higher rate of comorbidities [8], thus further complicating their care while the root cause of their issue remains unaddressed.…”
Section: Introductionmentioning
confidence: 99%